A Study the Water Quality Measuring Equipment with Automatic Sensor System: https://doi.org/10.69692/SUJMRD1004162 - NAMAVONG, Ten; LARKAENCHAN, Donekeo; SENGTHIPPANI, Tick; PARMANEE, Thay; DITTAPHONG, Xaysamone; SISOUPHANH, Vetmanysay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper studied the water quality in Dong Khoai Village, Xaythani District, Vientiane Capital, which is the primary water pumping location for agriculture. The area has a population of over 1735 citizens and cover more than 450 hectares. Common issue found in Markhiaw river. Stream is its toxicity to certain rice field, causing it inability to grow rice despite using fertilizer. Furthermore, this stream gives dissatisfaction odor, negatively affects people who get into the water for fishing and occasionally found death fish in the areas. In order to assess the water quality and disseminate the results to the public. Therefore, this study aims to investigate the creating of an automated sensor system for high precision water quality monitoring in the water. Four sensors; pH (hydrogen potential), EC (electro conductivity), TDS (total dissolved solid), and temperature are used in this procedure. The sensor system was tested, and build a small station uses solar energy and saves information into the SD card and available online by Blynk, and compare the test results with national environmental standards. The research revealed that, in comparison to the standard instrument S5 pro parameter, the measuring stations for the water quality values of all four sensors are accuracy value of 92.91% to 99.34%. Based on the information gathered over the course of two months, from February 13 and March 18, the pH value will be low, at 5. The pH value is high, at 11, between 13, 17 and 18 February 2024. These numbers are considered to be in the standard ranks. Regarding the dissolved solids in the water vary from 3 to 100 mg/L, and the electrical conductivity is between 100 and 180 µS/cm. They are also fall upon the National Environmental Standard. The Temperature value is high, at 40.81 ºC on 4 February 2024 and from 02 March 2024, the Temperature value will be low, at 24.4ºC.